Copyright Application for Students' Work at State Vocational High School 1 Demak Multimedia Majors - Kusmaningtyas, Rindia Fanny; Rahayu, Sang Ayu Putu; Hidayat, Arif (Indonesian Journal of Advocacy and Legal Services, 2021)
High School (SMK) is one of the educational institutions responsible for creating human resources that have skills so that at the time of graduation can develop performance in the world of work. most vocational school students who take multimedia corner where currently have spawned creative works. The existence of Law Number 28 of 2014 concerning Copyright is very important for the existence of legal protection for the copyrighted works of SMK students in the multimedia field. Because of the importance of understanding copyright and its legal protection. The targets of this activity are students of SMK N 1 Demak majoring in Multimedia, which are expected to develop their potential in finding creative works and knowing their benefits and legal protection. The method used in overcoming problems regarding developing the potential of SMK students in creating creative works. So that SMK students know the legal protection and benefits of copyrighted works and understand things that can be categorized as copyright works, who has the right to be the copyright holder, and what actions can violate Rights in accordance with Law Number 28 of the Year 2014 concerning Copyright. The steps taken to address the issues described above are: (1) Development or socialization of copyright recognition; dan (2) Coaching in developing the potential of vocational school students in creating copyrighted works.